Tuberous sclerosis with follicular repigmentation. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
Pigment reoccurrence inside a white cutaneous stain can occur with different mechanisms. Characteristically, in piebaldism round, large islands of normal or accentuated pigmentation appear; their appearance seems to be independent of sun exposure (1). In nevus depigmentosus lesions reminiscent of lentigines may occur as a result of reverse mutation (2). A follicular repigmentation, that is, a progressive melanocyte repopulation of the epidermis basal layer starting from the hair follicle melanocytes, occurs in vitiligo, especially in the perinevic and segmental forms that more easily tend to regress as compared with systemic vitiligo. On the other hand, to the best of our knowledge a follicular repigmentation of a white macula of tuberous sclerosis complex has never been described so far in the relevant literature.